Gambaran Ketergantungan Gadget pada Anak Usia Sekolah - Nurfitri Rahmawati; Herlina Herlina; Yesi Hasneli N. (Jurnal Keperawatan, 2021)
Excessive usage of gadgets can lead to addiction for school-age children, which has some impacts on the child's physical and psychosocial development. This study aims to describe the dependence of gadgets on school-age children. This study used a descriptive design. The sample of this study was 30 respondents who were taken by non-probability sampling technique, namely purposive sampling. The measuring instrument of this study was the Smartphone Addiction Scale Short Version (SAS-SAV) questionnaire. Data analysis used simple descriptive. Most of respondents were 11 years old (66.7%), boy (70%), first-born (36.7%), fifth grade (70.0%), application used was games (83.3%), usage time of gadget was 1-2 hours (36.7%) and the owner of gadget for respondents was their parents (63.3%). The results of this study indicate that more than half of the respondents who are addicted to gadgets are 53.3%. This study recommends to community, especially families, to be able to monitor their children in the usage of gadget and can prevent gadget addiction in school-age children.